Definition, Detection, Skills Acquisition and Professional Background Developmentin the ICT Industry - Olmedo Torre, Noelia; Farrerons Vidal, Óscar (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2014)
This article is concerned with the detection of training requirements needed by a professional in the multimedia industry of the TIC sector by means of defining his or her professional abilities. Any detected deficiencies will be the basis for training course recommendations for a particular professional profile. They will have the support from the training programs of the LAM (Laboratory of Multimedia Applications) based on a training model that we call “hybrid”. This is used for the production and integration of training matters and for virtual places of learning. The contribution of this investigation will be basically towards the display and definition of the profiles and their professional abilities within the multimedia sector of the TIC companies. It also provides the detection, promotion and orientation of the needs for sufficient training. The method is applicable to other profiles and in other professional sectors.